ANALISIS KINERJA PERUSAHAAN STARTUP DIPENGARUHI LINGKUNGAN KERJA DAN KOMPENSASI YANG DIMEDIASI BEBAN KERJA KARYAWAN - Iwan Kresna Setiadi; Rafif Zuhairrahman; Yudi Nur Supriadi (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
The purpose of this study is to determine the role of workload mediation on performance influenced by the work environment and compensation  of start-up  companies with workload as a mediating variable carried out on Startup Logistics employees. The respondents in this study were 155 employees  of DKI Jakarta Logistics Startup. Banten, and Bogor.by using sampling techniques that make all members of the population as samples. The analysis technique used is the path analysis method and data processing is carried out through SmartPLS 4.0. The results of testing this study show that  the work environment has no effect and is not significant on the performance of the Startup company, (2) compensation has an effect and is significant on the performance of the Startup company, the workload-mediated work environment has an effect and is significant on the performance of  the Startup company , workload-mediated compensation has an  effect and is significant on the performance of the Startup company, the work environment has no effect and is not significant on the performance of the Startup company. This research is very useful for companies to consider that in order for employee performance to increase, a balanced workload mediation role is needed, as well as a good work environment and fair compensation and employee welfare